2017
DOI: 10.1515/afmnai-2017-0011
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Course and Termination of the Cephalic Vein in the Deltopectoral Triangle

Abstract: The knowledge of cephalic vein variation would aid proper identification and prevent error in surgical emergencies. The path, distribution, and termination of the cephalic vein in relation to the deltopectoral triangle were studied in twenty formalin-embalmed cadavers.Results show the bilateral presentation of the cephalic vein in all the shoulders examined. Thirtyseven (37) cases presented with a superficial and lateral course of the cephalic vein in the deltopectoral groove, while the rest three cases presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The incidence of a cephalic vein with a supraclavicular course was reported in 2% to 10% of cases in previous reports, comparable to the 3.8% of cases identified in the current study. 12,13 In the present study, venograms of arms with a previous access history were excluded to avoid confounding the original vein anatomy by previous access placements, whereas substantial proportions of patients with previous access history were included in previous reports. 4,5 In addition, previous studies either did not describe Asian patients as part of their study populations or the numbers of Asian patients included in these studies were too small; furthermore, some types of anatomical variants have not been observed in Asian groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of a cephalic vein with a supraclavicular course was reported in 2% to 10% of cases in previous reports, comparable to the 3.8% of cases identified in the current study. 12,13 In the present study, venograms of arms with a previous access history were excluded to avoid confounding the original vein anatomy by previous access placements, whereas substantial proportions of patients with previous access history were included in previous reports. 4,5 In addition, previous studies either did not describe Asian patients as part of their study populations or the numbers of Asian patients included in these studies were too small; furthermore, some types of anatomical variants have not been observed in Asian groups.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of a cephalic vein with a supraclavicular course was reported in 2% to 10% of cases in previous reports, comparable to the 3.8% of cases identified in the current study. 12,13…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study [ 7 ], two out of thirty-seven (5.4%) cases had cephalic vein crossed anteriorly and above the lateral third of the clavicle and terminated in the neck by draining directly into the external jugular vein. Loukas et al [ 10 ] found a collateral branch between the cephalic and the external jugular vein in 2% of 200 limbs examined.…”
Section: Discussionmentioning
confidence: 99%
“…Anastasopoulos et al [ 6 ] reported in 2% of cases the occurrence of anastomosis of cephalic vein with external juguar vein (EJV) via a communicating branch. Knowledge of these variations is essential to clinicians and surgeons for venous access during emergencies and surgery [ 7 ]. In this report, we describe a case of an anomalous cephalic vein with a bifid course of terminations on both left and right upper limbs which has not been described by the previous literature.…”
Section: Introductionmentioning
confidence: 99%